2021
DOI: 10.1016/j.jbc.2021.100324
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock transcription factor 1 is SUMOylated in the activated trimeric state

Abstract: The heat shock response is a transcriptional program of organisms to counteract an imbalance in protein homeostasis. It is orchestrated in all eukaryotic cells by heat shock transcription factor 1 (Hsf1). Despite very intensive research, the intricacies of the Hsf1 activation-attenuation cycle remain elusive at a molecular level. Post-translational modifications belong to one of the key mechanisms proposed to adapt the Hsf1 activity to the needs of individual cells, and phosphorylation of Hsf1 at multiple site… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Histone deacetylases are a target for a new class of anticancer drugs, some of which have been approved for the treatment of hematological malignancies ( 159 ). Other modes of HSF1 regulation include its SUMOylation ( 160 162 ) and a production of its differentially spliced isoforms ( 137 , 163 ).…”
Section: Hsf1mentioning
confidence: 99%
“…Histone deacetylases are a target for a new class of anticancer drugs, some of which have been approved for the treatment of hematological malignancies ( 159 ). Other modes of HSF1 regulation include its SUMOylation ( 160 162 ) and a production of its differentially spliced isoforms ( 137 , 163 ).…”
Section: Hsf1mentioning
confidence: 99%
“…48 For instance, in response to heat shock, cells activate signaling pathways, leading to the transient expression of protective heat shock proteins, 49 which are highly controlled by SUMOylation. [50][51][52] SUMOylation also plays important roles in the response to several conditions, such as virus infections, 53,54 and osmotic 55 and oxidative stress. 55 Regarding ischemic stress, to date, most studies of SUMOylation and ischemia have focused on the neuronal tissue, evaluating the role of protein SUMOylation after strokes.…”
Section: Sumoylation During Low-perfusion Pathological Statesmentioning
confidence: 99%
“…In general, protein SUMOylation increases in response to a variety of cell stressors 48 . For instance, in response to heat shock, cells activate signaling pathways, leading to the transient expression of protective heat shock proteins, 49 which are highly controlled by SUMOylation 50–52 . SUMOylation also plays important roles in the response to several conditions, such as virus infections, 53,54 and osmotic 55 and oxidative stress 55 …”
Section: Sumoylation During Low‐perfusion Pathological Statesmentioning
confidence: 99%
“…Surprisingly, this sumoylation event is not required for the induction of the heat‐shock response, but it rather suppresses HSF1 transactivation capacity [64–66]. A recent study showed, using purified proteins, that trimerized HSF1 is more efficiently sumoylated at K298 than monomeric HSF1, but sumoylation does not interfere with HSF1 DNA‐binding or HSC70‐mediated dissociation from DNA in vitro [67]. In contrast, sumoylation of HSF2 at K82 in the DBD inhibits its DNA‐binding activity [68–71].…”
Section: Posttranslational Modifications Regulate Hsf1 and Hsf2mentioning
confidence: 99%